Decentralized based Security Mechanism for Linking Sensitive Data using Blockchain Technology - Patil, Ashwini; Shelake, Vijay (International Journal of Computer Sciences and Engineering, 2023)
Privacy preservation practises intensify as data privacy infractions are an increasing source of worry. A lot of organisations gather a lot of data. Organisations occasionally utilise this data for a variety of activities. However, the data gathered may include sensitive or private information that has to be secured. If we disclose data for sharing purposes, privacy protection is a crucial problem. There are several methods for protecting privacy, but they are vulnerable to different kinds of assaults and data loss. In this research, we suggested a practical method for maintaining privacy via homomorphic encryption. Our method safeguards sensitive data with little information loss, improving data usefulness and guarding against many sorts of assault.